ESTUDIO ANÁTOMO-HISTOLÓGICO DEL APARATO REPRODUCTOR DE LA CODORNIZ HEMBRA, VARIEDAD JAPONESA (Coturnix coturnix v.japonica) - La Madrid T., Daniela (2002)
Morphological changes of the ovary and oviduct from birth until sexual maturation were monitored in 35 female quails. The birds were randomly selected from a flock reared at the quail farm of the Facultad de Medicina Veterinaria de la Universidad Nacional Mayor de San Marcos. Five quails were weighed and then slaughtered every week starting at one week of age. The ovaries were measured in situ, removed and processed for histological evaluation. Mean body weights and ovary length were 40, 68, 108, 132, 138, 171, and 154 g; and 6.9, 8.8, 11.6, 12.0, 11.8, 13.3, and 13.3 mm for the 1st, 2nd, 3rd, 4th, 5th , 6 th, and 7th week of age. Sexual maturity started at week 6. Histological images of growing and mature follicles coincided with macroscopic observations.